ADAPTATION OF FIRST-YEAR STUDENTS TO INDEPENDENT WORK IN HIGHER SCHOOL (Pedagogy of Higher and Secondary Education, 2001)
This article reveals the causes of difficulties in adaptation of first-year students to the training process in higher school and ways of their elimination. It concretizes the possibilities of independent work.